2017
DOI: 10.5152/eej.2017.16059
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy Resin-Based Root Canal Sealer Penetration into Dentin Tubules Does not Improve Root Filling Dislodgement Resistance

Abstract: Objective: This study sought to evaluate the effect of the penetration of an epoxy resin-based root canal sealer into dentin tubules on the force required to dislodge the root canal filling. Methods: Sixty extracted human central incisors with single canals were decoronated, instrumented, and filled with gutta-percha and AH Plus sealer labeled with 0.1% rhodamine B dye. The roots were further sectioned horizontally at 3, 6, and 8 mm from the apex. The coronal surfaces of the resulting 180 slices were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…In most parts of a specimen the dentinal tubule penetration is lower than the values used for statistical analysis. The thesis of overestimated dentinal tubule penetration is supported by recent findings that dentinal tubule penetration investigated by CLSM did not correlate with dislodgement resistance of root canal fillings [ 22 ].…”
Section: Discussionmentioning
confidence: 85%
“…In most parts of a specimen the dentinal tubule penetration is lower than the values used for statistical analysis. The thesis of overestimated dentinal tubule penetration is supported by recent findings that dentinal tubule penetration investigated by CLSM did not correlate with dislodgement resistance of root canal fillings [ 22 ].…”
Section: Discussionmentioning
confidence: 85%
“…It is worth remembering that the endodontic scientific community has been guilty of overestimating the relationship between logic, that is deductive reasoning, and reliable scientific evidence before. For example, De-Deus et al (2012, 2017b concluded that sealer penetration of dentinal tubules which had been used historically as an indication of the superiority of a given root filling technique or material had no basis in fact and that there was no experimental evidence to support that claim. Interestingly, that false rationale had also been used as promotional material to launch new root filling materials.…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) has been deployed in previous studies to highlight the sealer characterization, to analyze the sealer–dentin interface and sealer’s penetration into dentinal tubules [ 50 , 51 , 52 , 53 , 54 , 55 ]. In similar studies, a comparable number of samples were selected for SEM investigation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%